(untitled) (Transactions of the Association of European Schools of Planning, 2020)
Given the increasing number of people seeking refuge in Belgium and across Europe more broadly, it is essential that governments assume responsibility for the integration of refugees into society. An essential aspect of this process is the provision of a durable path from shelter to housing. Choosing a place of residence, and the success in obtaining suitable housing conditions, are factors that significantly shape the integration process. In the context of refugee settlement in Belgium, however, asylum and migration policies to date have been predominantly focused on tackling temporary crises with little consideration paid to long-term integration and housing strategies. Due to separated policy competences (reception at the federal policy level, and housing at the regional level), and the absence of a sense of responsibility from both Flemish (regional) and federal government, voluntary organisations have developed significant roles at the local level in the transition from shelter to housing, and in further housing needs of recognised refugees. Achieving this transition is impeded by capacity problems, discrimination, lack of local social networks, and limited timeframes. Using the concept of path dependency as a theoretical starting point, this article employs qualitative methods to highlight the impact of both asylum policies and the spatial characteristics of reception centres on transitions towards more permanent housing. Recommendations for refugee accommodation are made to enhance the transition from shelter to housing. Finally, it addresses alternative housing projects that are conducive to social integration as well as to the transition of refugees to the regular housing market.